Major Depressive Disorder in Long COVID and Exposure to Pro‐Inflammatory Cytokines During Infection by SARS‐CoV‐2 - Hernan F. Guillen‐Burgos; Juan F. Gálvez‐Flórez; Sergio Moreno‐López; Sabrina Wong; Angela T. H. Kwan; Mariana Ramirez‐Posada; Juan‐Manuel Anaya; Roger S. McIntyre (Psychiatric Research and Clinical Practice)
Objective Major Depressive Disorder (MDD) is common in long COVID syndrome; however, the neurobiological mechanisms are unclear. An immune activation response has been associated with COVID‐19 severity as well as in MDD. We hypothesize that high levels of pro‐inflammatory cytokines during SARS‐CoV‐2 infection may be associated with new‐onset MDD and severe outcomes such as treatment‐resistant depression (TRD) and risk of suicide ideation and behavior (SI/SB). Methods A case‐control nested to a cohort study was carried out on a total of 678 COVID‐19 survivors (MDD = 184 vs. non‐MDD = 494). A pro‐inflammatory panel of serum levels of cytokines (IL‐1β, IL‐4, IL‐6, IL‐8, IL‐13, IL‐17α, TNF‐α) was evaluated during COVID‐19 hospitalization and severe outcomes such as TRD and SI/SB were assessed in individuals with new onset of MDD after hospital discharge compared to non‐MDD COVID‐19 survivors. Results High levels of pro‐inflammatory cytokines during SARS‐CoV‐2 infection were identified in MDD participants compared to non‐MDD subgroups during long COVID. These differences were sustained also for TRD and SI/SB severity outcomes. There is a mild association of high levels of pro‐inflammatory cytokines and MDD, TRD, and SI/SB. Conclusion High levels of pro‐inflammatory cytokines during severe or critical COVID‐19 exposure may explain long COVID associated MDD and thus severe outcomes such as TRD and SI/SB. Relevance to clinical practice Identifying elevated pro‐inflammatory cytokines during COVID‐19 as a risk factor for MDD and severe outcomes underscores the need for early screening and targeted treatments in long COVID. Monitoring cytokine levels may help clinicians predict and manage TRD and SI/SB in this population, improving long‐term psychiatric outcomes.